Average Error: 0.2 → 0.1
Time: 4.9s
Precision: 64
$z - \frac{x \cdot y}{100}$
$z - x \cdot \frac{y}{100}$
z - \frac{x \cdot y}{100}
z - x \cdot \frac{y}{100}
double f(double z, double x, double y) {
double r2285457 = z;
double r2285458 = x;
double r2285459 = y;
double r2285460 = r2285458 * r2285459;
double r2285461 = 100.0;
double r2285462 = r2285460 / r2285461;
double r2285463 = r2285457 - r2285462;
return r2285463;
}


double f(double z, double x, double y) {
double r2285464 = z;
double r2285465 = x;
double r2285466 = y;
double r2285467 = 100.0;
double r2285468 = r2285466 / r2285467;
double r2285469 = r2285465 * r2285468;
double r2285470 = r2285464 - r2285469;
return r2285470;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.2

$z - \frac{x \cdot y}{100}$
2. Using strategy rm
3. Applied *-un-lft-identity0.2

$\leadsto z - \frac{x \cdot y}{\color{blue}{1 \cdot 100}}$
4. Applied times-frac0.1

$\leadsto z - \color{blue}{\frac{x}{1} \cdot \frac{y}{100}}$
5. Simplified0.1

$\leadsto z - \color{blue}{x} \cdot \frac{y}{100}$
6. Final simplification0.1

$\leadsto z - x \cdot \frac{y}{100}$

# Reproduce

herbie shell --seed 1
(FPCore (z x y)
:name "z - (x* y) / 100"
:precision binary64
(- z (/ (* x y) 100)))